Kth Root Transformation for a subclass of Log-Sigmoid Analytic Function based on Quasi-Subordination - Hari Priya, M.; Bharavi Sharma, R.; Suman Kumar, V. (International Journal of Engineering and Technology, 2018)
In the present investigation, using the concept of quasi-subordination, two subclasses of analytic functions have been introduced. The coefficient inequalities, the Fekete-Szego inequality, upper bounds for kthÂ root transformation were studied. This study is extended to function Â and for Â .Â